Transplant Experiments as a Tool for Evaluating the Suitability of Sessile Organisms as Biomonitor Species in Tropical Coastal Waters: The Case of the Brown Mussel Perna perna (Linnaeus, 1758) in Rio de Janeiro State, Brazil - Renan Thiago Laynes Longo; Petrus Magnus Amaral Galvão; Adan dos Santos Lino; João Paulo Machado Torres; Olaf Malm; Paulo Renato Dorneles (Orbital: The Electronic Journal of Chemistry, 2018)
The present study evaluates mercury (Hg) toxicokinetics in Perna perna (L.) mussels from tropical bays through transplantation experiments. The mussels were transplanted from Guanabara Bay (GB) to Ilha Grande Bay (IGB). The experiments were carried out in December 2008 (experiment 1) and June 2009 (experiment 2). Both experiments lasted one month. In the experiment 2, the transplanted animals (77±8 µg.kg-1) showed a significant increase in Hg concentrations and exhibited significantly higher Hg concentrations than the animals that remained in GB (41±4 µg.kg-1). Despite this increase in mercury levels, the transplanted animals have not achieved the Hg concentrations of IGB resident animals (100±11 µg.kg-1). These results suggest that individuals of this species rapidly incorporated Hg in tropical estuaries.DOI: http://dx.doi.org/10.17807/orbital.v10i4.1069